2008
DOI: 10.1152/physiolgenomics.00150.2007
|View full text |Cite
|
Sign up to set email alerts
|

Congenic strains reveal the effect of the renin gene on skeletal muscle angiogenesis induced by electrical stimulation

Abstract: de Resende MM, Amaral SL, Moreno C, Greene AS. Congenic strains reveal the effect of the renin gene on skeletal muscle angiogenesis induced by electrical stimulation. Physiol Genomics 33: 33-40, 2008. First published January 15, 2008 doi:10.1152/physiolgenomics.00150.2007.-Previous studies have indicated the importance of angiotensin II (ANG II) in skeletal muscle angiogenesis. The present study explored the effect of regulation of the renin gene on angiogenesis induced by electrical stimulation with the use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
32
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 57 publications
(47 reference statements)
2
32
0
Order By: Relevance
“…The SS/MCWi rat has been inbred from the DahlS parent strain at the Medical College of Wisconsin and exhibits both saltsensitive hypertension and microvascular rarefaction (3,5). Recent work has also shown that BMMNC derived from the SS/MCWi rat are not capable of inducing neovascularization in a hindlimb angiogenesis model (6).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The SS/MCWi rat has been inbred from the DahlS parent strain at the Medical College of Wisconsin and exhibits both saltsensitive hypertension and microvascular rarefaction (3,5). Recent work has also shown that BMMNC derived from the SS/MCWi rat are not capable of inducing neovascularization in a hindlimb angiogenesis model (6).…”
mentioning
confidence: 99%
“…Recent work has also shown that BMMNC derived from the SS/MCWi rat are not capable of inducing neovascularization in a hindlimb angiogenesis model (6). Genetic introgression of chromosome 13 from the nonhypertensive Brown Norway (BN) rat onto the SS/MCWi background (SS-13 BN /MCWi rat) rescues the SS/MCWi rat from salt-sensitive hypertension and vessel rarefaction (5) and also restores the capability of BMMNC to promote skeletal muscle angiogenesis (6). Thus there is a gene or genes located on chromosome 13 important for the therapeutic efficacy of BMMNC for neovascularization in the hindlimb.…”
mentioning
confidence: 99%
“…The RAS has long been known to be an essential modulator of sodium homeostasis and vascular resistance. Recently increasing evidence has implicated this system in the control of microvascular density since inhibition of the RAS pharmacologically (3,4,19,27,44), genetically (5,14), and by high-salt diet (15,16,50,51) inhibits angiogenesis. Others have described local tissue RAS in a variety of organs that act both independently and in concert with the circulating system (22,35,43,47).…”
mentioning
confidence: 99%
“…In this lowrenin model of hypertension, impaired regulation of the RAS results in reduced microvascular density (44) and an inhibited angiogenic response in skeletal muscle (3,4), both of which can be ameliorated by a subpressor administration of ANG II (16,51). In previous studies we have shown that the angiogenic phenotype in the SS rat can also be restored through introgression of a portion of chromosome (Chr) 13 from Brown Norway BN/NHsdMcwi (BN) that contains the renin gene and is as small as 4.05 Mb (14). Interestingly, sequencing studies have revealed that there are no differences in the coding region or the 5=-flanking proximal promoter region of the renin gene between SS and BN rats.…”
mentioning
confidence: 99%
See 1 more Smart Citation